Correlation of matrix metalloproteinase 3 and matrix metalloproteinase 9 levels with non-motor symptoms in patients with Parkinson’s disease - Liu, Chuan Ze; Guo, Da Shuai; Ma, Jian Jun; Dong, Lin Rui; Chang, Qing Qing; Yang, Hong Qi; Liang, Ke Ke; Li, Xiao Huan; Yang, Da Wei; Fan, Yong Yan; Gu, Qi; Chen, Si Yuan; et al. (Frontiers in Aging Neuroscience, 2022)
Objective: Matrix metalloproteinases (MMPs) are essential for tissue formation, neuronal network remodeling, and blood–brain barrier integrity. Matrix metalloproteinases have been widely studied in acute brain diseases. However, the relationship with Parkinson's disease (PD) remains unclear. The purpose of this study was to evaluate the serum MMP3 and MMP9 levels of PD patients and analyze their correlation with nonmotor symptoms. Methods: In this cross-sectional study, we recruited 73 patients with idiopathic PD and 64 healthy volunteers. Serum MMP3 and MMP9 levels were measured by enzyme-linked immunosorbent assay (ELISA). Patients with PD were assessed for nonmotor symptoms using the Nonmotor Symptoms Scale (NMSS) and Parkinson's disease sleep scale (PDSS) and Mini Mental State Examination (MMSE). Results: Serum MMP3 levels were significantly decreased in PD patients, predominantly those with early-stage PD, compared with controls [12.56 (9.30, 17.44) vs. 15.37 (11.33, 24.41) ng/ml; P = 0.004], and the serum MMP9 levels of PD patients were significantly higher than those of healthy controls [522 (419, 729) vs. 329 (229, 473) ng/ml; P < 0.001]. MMP3 levels were positively correlated with the NMSS total score (r = 0.271, P = 0.020) and the single-item scores for item six, assessing the gastrointestinal tract (r = 0.333, P = 0.004), and there was an inverse correlation between serum MMP3 levels and PDSS score (r = −0.246, P = 0.036); meanwhile, MMP9 levels were positively correlated with the NMSS total score (r = 0.234, P = 0.047), and higher serum MMP9 levels were detected in the cognitive dysfunction subgroup than in the cognitively intact subgroup [658 (504, 877) vs. 502 (397, 608) ng/ml, P = 0.008]. Conclusion: The serum MMP3 level of PD patients (especially early-stage patients) was significantly lower than that of the healthy control group, and the MMP9 level was significantly higher than that of the healthy control group. MMP3 and MMP9 levels correlate with sleep disturbance and cognitive function in PD patients, respectively.